Enhancing MSME Income in North Sumatra through E-Accounting: Examining the Role of Accounting Literacy from a Maqasid al-Shariah Perspective - Yenni Arafah; Andri Soemitra; Nurlaila Nurlaila (Program Pascasarjana IAIN Langsa, 2025)
This study examines the impact of E-Accounting on the revenue of MSMEs in North Sumatra Province, addressing the gap in existing literature regarding the role of accounting literacy. The study also explores the challenges faced by MSMEs in adopting E-Accounting. Using a mixed-methods approach with an exploratory sequential design, quantitative data were collected through structured questionnaires from 271 MSMEs across seven districts/cities, analyzed using PLS-SEM. Qualitative data were gathered from in-depth interviews with 20 purposively selected MSMEs. The results show that E-Accounting significantly positively affects MSME revenue, but accounting literacy does not serve as a significant moderating variable, implying that the benefits of E-Accounting in increasing revenue do not rely solely on the users' accounting knowledge. Qualitative findings indicate that while MSMEs recognize the benefits of E-Accounting, they use it mainly for administrative tasks rather than strategic decision-making. Common challenges include limited digital infrastructure, lack of training, and dependence on intuition. The novelty of this research lies in the integration of Sharia principles, such as amanah and hifz al-mal, offering insights into how Islamic values shape MSME financial practices. This study provides practical, culturally relevant recommendations for improving E-Accounting adoption and enhancing MSMEs' financial resilience through the alignment of technology and ethics.